"A bridge too far?" Ideas, employment relations and policy‐making about the future of work. Issue 1 (30th November 2021) - Ainsworth, Susan; Knox, Angela
Abstract: Drawing on ideational perspectives, we examine how ideas about the future of work and the discursive forms they take contribute to policy‐making about employment relations and labor markets. Analyzing data from an Australian government Inquiry reporting on the future impact of technological and other work changes, we find that rather than being about these topics, the Inquiry focuses more on actors' ideas regarding the present state of employment relations and education. Moreover, the incomplete nature of actors' narratives, particularly about the temporally distant future, may account for government's unwillingness and/or lack of preparedness to make more radical changes.